Real-world clinical effectiveness of Tixagevimab/Cilgavimab and Regdanvimab monoclonal antibodies for COVID-19 treatment in Omicron variant-dominant period - Fomina, Daria S.; Lebedkina, Marina S.; Iliukhina, Anna A.; Kovyrshina, Anna V.; Shelkov, Artem Y.; Andreev, Sergey S.; Chernov, Anton A.; Dolzhikova, Inna V.; Kruglova, Tatyana S.; Andrenova, Gerelma V.; Tukhvatulin, Amir I.; Shcheblyakov, Dmitry V.; et al. (Frontiers in Immunology, 2023)
Several virus-neutralizing monoclonal antibodies (mAbs) have become new tools in the treatment of the coronavirus disease (COVID-19), but their effectiveness against the rapidly mutating virus is questionable. The present study investigated the effectiveness of Tixagevimab/Cilgavimab and Regdanvimab for mild and moderate COVID-19 treatment in real-world clinical practice during the Omicron variant-dominant period. Patients with known risk factors for disease progression and increasing disease severity were enrolled in the study within the first 7 days of symptom onset. Seventy-seven patients were divided into four groups: first 15 patients received 300 mg Tixagevimab/Cilgavimab intravenously (IV) and 23 patients got the same drug 300 mg intramuscularly (IM), the next 15 patients was on the same combination in dose of 600 mg IV, and 24 patients were on Regdanvimab at a dose of 40 mg/kg IV. By Day 4, 100% of Tixagevimab/Cilgavimab IV patients showed negative polymerase chain reaction results for SARS-CoV-2 Ribonucleic acid (RNA) regardless of the mAbs dose while in the Regdanvimab group 29% of the patients were positive for SARS-CoV-2 virus RNA. The testing for virus neutralizing antibodies (nAbs) to various Omicron sublineages (BA.1, BA.2, and BA.5) showed that an increase in nAb levels was detected in blood serum immediately after the drug administration only in Tixagevimab/Cilgavimab 300 mg and 600 mg IV groups. In the group of intravenous Regdanvimab, a significant increase in the level of nAbs to the Wuhan variant was detected immediately after the drug administration, while no increase in nAbs to different Omicron sublineages was observed. Clinical trial registration https://clinicaltrials.gov/, identifier NCT05982704.